2009
DOI: 10.1086/598342
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Animal and Human Prions by Hydrogen Peroxide Gas Plasma Sterilization

Abstract: Prions cause various transmissible spongiform encephalopathies. They are highly resistant to the chemical and physical decontamination and sterilization procedures routinely used in healthcare facilities. The decontamination procedures recommended for the inactivation of prions are often incompatible with the materials used in medical devices. In this study, we evaluated the use of low-temperature hydrogen peroxide gas plasma sterilization systems and other instrument-processing procedures for inactivating hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 27 publications
0
52
0
1
Order By: Relevance
“…Studies that have used these methods have reported survival of prion infectivity after autoclaving at 134°C for 18 minutes or more (Table 2). 13-16,19,20,22 Two studies in particular reported survival of infectivity despite subjecting the wires to detergent washing before autoclaving at 134°C for 18 minutes. 15,19 In these same studies, a decontamination protocol with sodium hydroxide (NaOH) treatment followed by autoclaving at 134°C for 18 minutes was not completely effective, which indicates that prion sterilization protocols that combine chemical treatment with autoclaving should be carefully selected.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that have used these methods have reported survival of prion infectivity after autoclaving at 134°C for 18 minutes or more (Table 2). 13-16,19,20,22 Two studies in particular reported survival of infectivity despite subjecting the wires to detergent washing before autoclaving at 134°C for 18 minutes. 15,19 In these same studies, a decontamination protocol with sodium hydroxide (NaOH) treatment followed by autoclaving at 134°C for 18 minutes was not completely effective, which indicates that prion sterilization protocols that combine chemical treatment with autoclaving should be carefully selected.…”
Section: Resultsmentioning
confidence: 99%
“…Two additional sterilization modalities are currently being developed: hydrogen peroxide gas vapor sterilization (e.g., STERRAD Ò , Ethicon Inc., Somerville, NJ), and ozone sterilization (TSO3 Inc., Dalton, Quebec, Canada) [13,14]. At this time, both are unavailable for clinical use with flexible endoscopes in the United States.…”
Section: Resultsmentioning
confidence: 99%
“…The current recommendation is to quarantine or incinerate surgical instrumentation after contact with contaminated patients, which is expensive and cumbersome [7,38]. Prions are unusually resistant to disinfection by conventional chemical high-level disinfectants/sterilants [13,39]. Variant Creutzfeldt-Jakob disease (vCJD) seems to be mainly transferred by consumption of beef products containing the bovine spongiform encephalopathy agent [38].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, any potential risk of recontamination is greatly reduced. Also, because the devices can be stored in a sterile manner until they are needed, the hospital saves valuable time [ 309]. Lastly, the STERRAD system takes up minimal room and necessitates no extra venting or separate water connections.…”
Section: Gas Plasma (Sterrad) Sterilizationmentioning
confidence: 99%